Increasing Student Knowledge and Skills in Utilizing Google Apps - Ibnur Rusi; Ilhamsyah; Renny Puspita Sari; Dian Prawira; Nurul Mutiah; Ferdy Febriyanto; Syahru Rahmayuda (Universitas Lancang Kuning, 2023)
ICT contributes to the sustainability of modern society, which demands effectiveness and efficiency in every activity carried out. One form of ICT is an application on Google Apps that can support the effectiveness and efficiency of the activities carried out. SMAN 1 Kakap is one of the schools in Kubu Raya Regency, West Kalimantan. SMAN 1 Kakap continues to improve quality, including improving students' abilities and skills in using ICT. Based on observations, there are problems by students of SMAN 1 Kakap, namely the lack of knowledge and skills of students in working together to complete group assignments effectively and efficiently through the application of ICT, they are not familiar with applications that can be used in completing collaborative tasks, besides that they do not know how to use Google Apps that can support activity efficiency. Community Service (CM) carried out by the Information Systems Department of Tanjungpura University aims to find solutions to problems faced by students of SMAN 1 Kakap. The form of PKM is in the form of knowledge transfer and training on using the Google Apps application to support collaborative tasks. The evaluation was carried out two times by administering questionnaires, namely before and after the activity, aiming to determine the level of success of the training provided. Based on the results of the evaluation, there was an increase in the knowledge and skills of SMAN 1 Kakap students in using Google Apps by 36.99%.